Platypnea-orthodeoxia syndrome in SARS-CoV-2 related ARDS: a case report - Aprea, Concetta; Imbriani, Simona; Cirigliano, Giovanna; Gjeloshi, Klodian; Meo, Luciana Agnese; Padula, Andrea; Ranieri, Roberta; Ricozzi, Carmen; Ruosi, Carolina; Cozzolino, Domenico; Adinolfi, Luigi Elio; Nevola, Riccardo (Acta Biomedica Atenei Parmensis, 2022)
Platypnea-Orthodeoxia Syndrome (POS) is an often misdiagnosed clinical condition characterized by dyspnea and hypoxia in sitting or semi-sitting position, reversible in supine position. Although POS is typically associated with intracardiac shunts, it seems frequent also in SARS-CoV-2 related Acute Respiratory Distress Syndrome (ARDS). In fact, the prevalent involvement of the lung bases due to interstitial pneumonia can determine refractory positional hypoxemia, with marked desaturation in the sitting position and regression or improvement in the supine position, configuring the clinical picture of the POS. We present a clinical case of POS associated with acute respiratory distress from SARS-CoV-2 pneumonia in which refractory hypoxia would have required support by invasive mechanical ventilation if the syndrome had not been identified.